BACTERIAL ISOLATES AND THEIR ANTIBIOGRAM FROM GENITAL DISCHARGES OF PUERPERAL AND REPEAT BREEDING CROSSBRED COWS - RAVAL, SR; PANCHAL, MT; DHAMI, AJ; HADIYA, KK; BHANDERI, BB (The Indian Journal of Animal Reproduction, 2017)
The study was conducted on early postpartum (25±2 days PP, n=30) and repeat breeder (RB, n=40) crossbred cows to evaluate genital infections, their antibiogram and fertility following use of suitable antibiotics. The puerperal discharges of 19 (63.3%) cows and CVM of 28 (70.0%) RB cows yielded bacterial isolates of mixed infection, Gram-positive bacilli/rods, Streptococcus spp., Gram-negative bacilli/rods, E. coli, Corynebacterium, Micrococcus spp., Streptococcus spp., Micrococcus spp. and Anthracoid, whereas the rest of the samples were sterile. The sensitivity of isolates to 13 antibacterial drugs tested ranged between 5.3-63.2% among puerperal cows and between 25.0-50.0% in RB cows, with the highest sensitive to Gentamicin (63.2 and 50.0%) and maximum resistance to Peniclillin (94.7%) in both groups. The cows yielding bacterial isolates in both groups were treated with sensitive antibiotics (i.m.) for 3-5 d and those not yielding bacterial growth served as controls. The animals were inseminated at subsequent estruses and followed for repeating to estrus for three cycles and/or pregnancy. Overall pregnancy rates in PP treated and control cows was 47.4% and 63.6%, respectively. Overall pregnancy rates in RB treated and control cows was 57.1% and 66.7%, respectively. In brief, variable prevalence of genital infections observed in early postpartum and repeat breeder cows indicated bacterial invasion with gentamicin being the highest effective antibiotic. The cows failing to get pregnant in the absence of bacterial growth indicated involvement of other reasons for repeating to estrus.
Keywords: Antibiogram; Cows; fertility; Puerperal endometritis; Repeat breeding